Pluralism and Equality in the Perspective of Human Rights in Indonesia - Abustan (Universitas Muhammadiyah Malang, 2023)
Abstract In the context of Indonesia's plural society, where the demand for pluralism is increasingly urgent during the democratic transition, it often raises questions about how the implementation of the principle of equality can be the foundation of democracy and the fulfillment of human rights. The purpose of writing is to analyzehow society respects pluralism/equality as part of the fulfillment of citizens' rights in a democratic country. The research method used is normative juridical by referring to legal norms contained in the constitution and legislation. The aim of the research is to identify the important dimensions that the state must consider in realizing pluralism and equality from the perspective of human rights in Indonesia. Moreover, it aims to demonstrate that in a diverse society, religious tolerance in the effort of developing religious life can still run harmoniously, dialogically, and tolerantly in the present modern Indonesia era. This is especially important for Indonesia, as it has the fourth-largest population in the world. Therefore, the presence of the state in supporting the multicultural democratic society is highly needed. Keywords: Plurality and Equality; Human Rights; and Democracy. Abstrak Dalam konteks masyarakat Indonesia yang plural, di mana tuntutan akan paham kemajemukan semakin mendesak pada masa transisi demokratisasi, sehingga kerap kali mengimbulkan pertanyaan bagaimana penerapan prinsip kesetaraan dapat menjadi landasan perjuangan demokrasi dan pemenuhan hak asasi manusia. Pertanyaan tersebut itulah yang menjadi fokus riset ini, yakni meneliti tentang bagaimana tatanan masyarakat menghormati kemajemukan/kesetaraan sebagai bagian dari pemenuhan hak-hak warga negara dalam sebuah negara demokrasi. Metode penelitian ini menggunakan metode Yuridis Normatif yaitu dengan mengacu pada norma-norma hukum yang terdapat dalam konstitusi dan peraturan perundang-undangan. Tujuan penelitian mengetahui dimensi-dimensi penting yang menjadi perhatian negara dalam mewujudkan kemajemukan dan kesetaraan dalam perspektif hak asasi manusia di Indonesia. Lebih dari itu, juga hendak menunjukkan bahwa dalam ranah masyarakat majemuk, toleransi agama dalam upaya pengembangan kehidupan beragama tetap berjalan harmonis, dialogis, dan toleran dalam era Indonesia moderen sekarang ini. Apalagi Negara Indonesia dengan jumlah populasi penduduk terbesar ke 4 di dunia. Maka dari itu, kehadiran negara dalam rangka menopang pilar masyarakat demokratis multikultural sangat diperlukan. Kata kunci: Kemajemukan dan Kesetaraan, Hak Asasi Manusia dan Demokrasi.